Aerobic Exercise: Randomized Controlled Trial Data Suggest Qualified Benefits for Erectile Dysfunction - Andrade, Chittaranjan (The journal of clinical psychiatry, 2024)
Erectile dysfunction (ED) refers to the difficulty in achieving and maintaining a degree of penile erection that suffices for satisfactory sexual activity. ED is multifactorial in origin; its prevalence therefore varies with the population studied. In the general population, ED is present in 18-52% of men in younger to older age groups and in 43-76% of men with different medical conditions. Phosphodiesterase-5 inhibitor drugs are gold standard treatments for ED. However, because many lifestyle disorders predispose to ED and because aerobic exercise is beneficial for these lifestyle disorders, aerobic exercise may be a possible intervention for ED. In this context, a recent systematic review and meta-analysis identified 11 randomized controlled trials (RCTs; pooled N = 1,147) of aerobic exercise vs nonexercising control conditions for the treatment of ED. These RCTs had been conducted in men with different medical and surgical conditions, commonly obesity, metabolic syndrome, diabetes mellitus, and cardiovascular disease. The exercise interventions were varied but mostly involved 30-60 minutes sessions of activity, 3-5 times a week, for a median duration of 6 months. Advice for diet and weight loss was also commonly provided. The meta analysis found that aerobic exercise was significantly superior to nonexercising control conditions, with greater improvement in erectile functioning observed in subjects with greater baseline impairment. Limitations of the findings were that subjects could not be blinded to the nature of the intervention and that the magnitude of benefit with exercise, although statistically significant, fell below thresholds suggested for clinical significance. Aerobic exercise might therefore be more useful for the primary prevention of ED, for which preliminary evidence already exists. Exercise can also be recommended, along with other lifestyle guidance, to improve sexual functioning in both men and women and to improve health across a range of domains.